Odpowiedzi

Najlepsza Odpowiedź!
2010-01-30T20:47:24+01:00
A) x³+x-2=0
x4=0-2
x4= -2 | : 4
x = - 0,5
b)x³+3x+4=0
6x= -4 | :6
x= - 0,67
c)4x³-3x-1=0
4x = -1 | :4
x= - 0,25
d)x⁴-x²-12=0
2x = 12 | :2
x = 6
e)x³+4x²-2x-8=0
9x = 8 | :9
x = 0,89
f)x³-3x²+4x-12=0
6x = 12 | :6
x = 2
g)x+4x³-x²-4=0
6x = 4 | :6
x = 0,67
h)2x³+7x²+7x+2=0
21x = -2 | :21
x = - 0,10
i)3x³-7x²-7x+3=0
-10x = -3 | : - 10
x = 0,3
j)4x³-13x²-13x+4=0
-35x = -4 | : - 35
x = 0,11
k)5x³+21x²-21x-5=0
10x = 5 | :10
x = 0,5
Liczę na naj :)
1 1 1
2010-01-31T00:04:39+01:00
A) x³ + x - 2 = 0
x4 = 0 - 2
x4 = -2 | : 4
x = - 0,5

b) x³ + 3x + 4 = 0
6x = -4 | :6
x = - 0,67

c) 4x³ - 3x - 1 = 0
4x = -1 | :4
x = - 0,25

d) x⁴ - x² - 12 = 0
2x = 12 | :2
x = 6

e) x³ + 4x² - 2x - 8 = 0
9x = 8 | :9
x = 0,89

f) x³ - 3x² + 4x - 12 = 0
6x = 12 | :6
x = 2

g) x + 4x³ - x² - 4 = 0
6x = 4 | :6
x = 0,67

h) 2x³ + 7x² + 7x + 2 = 0
21x = -2 | :21
x = - 0,10

i) 3x³ - 7x² - 7x + 3 = 0
-10x = -3 | : - 10
x = 0,3

j) 4x³ - 13x² - 13x + 4 = 0
-35x = -4 | : - 35
x = 0,11

k) 5x³ + 21x² - 21x - 5 = 0
10x = 5 | :10
x = 0,5